Relationship between L-DOPA-induced reduction in motor and exploratory activity and degree of DAT binding in the rat - Nikolaus, Susanne; Beu, Markus; De Souza Silva, Angelica Maria; Huston, Joseph P.; Hautzel, Hubertus; Chao, Owen Y.; Antke, Christina; Müller, Hans-Wilhelm (Frontiers in Behavioral Neuroscience, 2014)
Purpose: The present study assessed the influence of L-DOPA administration on neostriatal dopamine (DA) transporter (DAT) binding in relation to motor and exploratory behaviors in the rat. Methods: Rats received injections of 5 mg/kg L-DOPA, 10 mg/kg L-DOPA or vehicle. Motor and exploratory behaviors were assessed for 30 min in an open field prior to administration of [123I]FP-CIT. Dopamine transporter binding was measured with small animal single-photon emission computed tomography (SPECT) 2 h after radioligand administration for 60 min. Results: Both L-DOPA doses significantly reduced DAT binding and led to significantly less head-shoulder motility and more sitting relative to vehicle. Moreover, 10 mg/kg L-DOPA induced less distance traveled and ambulation than 5 mg/kg L-DOPA. Analysis of time-behavior (t-b) curves showed that L-DOPA-treated animals relative to vehicle exhibited (1) a faster rate of increase in duration of sitting; (2) a slower rate of increase in duration of head-shoulder motility; and (3) a slower rate of decrease in frequency of head-shoulder motility. Conclusions: The reductions of striatal DAT binding after L-DOPA challenges reflected elevated concentrations of synaptic DA. L-DOPA-treated animals showed less head-shoulder motility and more sitting than vehicle-treated animals, indicating an association between less behavioral activity and increased availability of striatal DA. The faster increase of sitting duration to a higher final level and the slower increase of head-shoulder motility to a lower final level relative to controls may be interpreted in terms on behavioral habituation to a novel environment.